High-yield production of 2D crystals by wet-jet milling - Antonio Esau Del Rio Castillo; Pellegrini, Vittorio; Ansaldo, Alberto; Ricciardella, Filiberto; Sun, Haiyan; Marasco, Luigi; Buha, Joka; Dang, Zhiya; Gagliani, Luca; Lago, Emanuele; Curreli, Nicola; Gentiluomo, Silvia; et al. (arXiv.org, 2018)
Efficient and scalable production of two-dimensional (2D) materials is required to overcome technological hurdles towards the creation of a 2D-materials-based industry. Here, we present a novel approach developed for the exfoliation of layered crystals, i.e., graphite, hexagonal boron nitride and transition metal dichalcogenides. The process is based on high-pressure wet-jet-milling (WJM), resulting in 2 L/hr production of 10 g/L of single- and few-layer 2D crystal flakes in dispersion making the scaling-up more affordable. The WJM process enables the production of defect-free and high-quality 2D-crystal dispersions on a large scale, opening the way for the full exploitation in different commercial applications, e.g., anodes active material in lithium ion batteries, reinforcement in polymer-graphene composites, and transparent conductors as we demonstrate in this report.